Assessing the Impact of Initiatives Aimed at Attaining Work-Life Balance on Lecturers’ Satisfaction in Academic Institutions in Uzbekistan - M. A. Kayumova (Вестник Российского экономического университета имени Г. В. Плеханова)
The work-life balance (WLB) is considered a crucial factor that influences well-being and productivity of academic personnel. Nature of academic duties, such as administrative, teaching, researching can cause stress and burningout, which negatively affects satisfaction with work and indices of retention. The article studies different initiatives aimed at raising WLB at academic institutions with focus at flexible schedule, possibility of distant work, complex programs of rehabilitation, policy favorable for the family and supporting practice of vocations. Data of the research show that flexible work schedules, such as controllable hours and hybrid models can seriously improve lecturers’ moral spirit and involvement. Apart from that, programs of rehabilitation aimed at physical and psychological health foster higher stability of work force. Policy favorable for the family includes prolonged leave for childcare, supports childcare and contributes to creation of inclusive environment, while adequate policy on vocations can make lecturers pay immediate attention to care for themselves. Results of the research underline the importance of institutional adherence to WLB initiatives as a strategic approach to building healthy and productive academic community. Admitting the priority of these initiatives education institutions can smooth unfavorable after-effects of stress at work place, raise satisfaction of the faculty and finally improve results of teaching.